Minimal contribution of cell-bound antibodies to the immunoscintigraphy of inflamed joints with 99mTc-anti-CD4 monoclonal antibodies - Kinne, R. W.; Wolski, A.; Palombo-Kinne, E.; Wolf, F.; Emmrich, F.; Becker, W. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: The cellular joint infiltrate in rheumatoid arthritis patients is rich in CD4-positive T-helper lymphocytes and macrophages, rendering anti-CD4 monoclonal antibodies (mAbs) suitable for specific immunoscintigraphy of human/ experimental arthritis. Following intravenous injection, however, mAbs are present both in the free form and bound to CD4-positive, circulating monocytes and T-cells. Thus, the present study aimed at analyzing the relative contribution of the free and the cell-bound component to the imaging of inflamed joints in experimental adjuvant arthritis (AA). Methods: AA rat peritoneal macrophages or lymph node T-cells were incubated in vitro with saturating amounts of 99mTc-anti-CD4 mAb (W3/25) and injected i.v. into rats with AA. Results: In vitro release of 99mTc-anti-CD4 mAb from the cells was limited (on average 1.57%/h for macrophages and 0.84%/h for T-cells). Following i.v. injection, whole body/joint scans and tissue measurements showed only negligible accumulation of radioactivity in inflamed ankle joints (tissue: 0.22 and 0.34% of the injected activity, respectively), whereas the radioactivity was concentrated in liver (tissue: 79% and 71%, respectively), kidney, and urinary bladder. Unlike macrophages, however, anti-CD4 mAb-coated T-cells significantly accumulated in lymphoid organs, the inflamed synovial membrane of the ankle joints, as well as in elbow and knee joints. Conclusion: While the overall contribution of cell-bound mAbs to the imaging of arthritic joints with anti-CD4 mAbs is minimal, differential accumulation of macrophages and T-cells in lymphoid organs and the inflamed synovial membrane indicates preferential migration patterns of these 2 cell populations in arthritic rats. Although only validated for 99mTc-anti-CD4 mAbs, extrapolation of the results to other anticellular mAbs with similar affinity for their antigen may be possible.
Keywords: Immunoscintigraphy; anti-CD4 mAb; macrophages; T-cells; adjuvant arthritis